The Emergence of the Global Fintech Market: Economic and Technological Determinants - Christian Haddad; Lars Hornuf (Center for Economic Studies and ifo Institute (CESifo), 2016)
We investigate the economic and technological determinants inducing entrepreneurs to establish ventures with the purpose of reinventing financial technology (fintech). We find that countries witness more fintech startup formations when the latest technology is readily available and people have more mobile telephone subscriptions. Furthermore, the available labor force has a positive impact on the development of this new market segment. Finally, the more sound the financial system, the lower the number of fintech startups in a country. Overall, the evidence suggests that fintech startup formation need not be left to chance, but active policies can influence the emergence of this new sector.
Keywords: L26; K20; O30; 330; fintech; entrepreneurship; startups; financial institutions